2014
DOI: 10.1002/ange.201310776
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Directional Control over Self‐Assembly Using Catalytic Micropatterned Surfaces

Abstract: Catalyst-assisted self-assembly is widespread in nature to achieve spatial control over structure formation. Reported herein is the formation of hydrogel micropatterns on catalytic surfaces. Gelator precursors react on catalytic sites to form building blocks which can self-assemble into nanofibers. The resulting structures preferentially grow where the catalyst is present. Not only is a first level of organization, allowing the construction of hydrogel micropatterns, achieved but a second level of organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“… 142 , 143 Recognizing catalyst-assisted self-assembly as a common process in nature to achieve spatial control over structure formation, they developed an ingenious way to generate a spatially controlled supramolecular hydrogel using a micropatterned catalyst on a surface. 144 According to their design, the precursors (cyclohexane-1,3,5-tricarbohydrazide and 3,4-bis[2-(2-methoxyethoxy)ethoxy]benzaldehyde, 3:1) of a gelator (trishydrazone derivative 144 ) react on micropatterned catalytic sites on a surface to form building blocks of self-assembled nanofibers that act as the matrixes of the hydrogels. Unlike homogeneous catalysis, this method apparently can achieve multilevel organization among the nanofibers, which is uniquely promising for further development.…”
Section: Stimuli For Hydrogelationmentioning
confidence: 99%
“… 142 , 143 Recognizing catalyst-assisted self-assembly as a common process in nature to achieve spatial control over structure formation, they developed an ingenious way to generate a spatially controlled supramolecular hydrogel using a micropatterned catalyst on a surface. 144 According to their design, the precursors (cyclohexane-1,3,5-tricarbohydrazide and 3,4-bis[2-(2-methoxyethoxy)ethoxy]benzaldehyde, 3:1) of a gelator (trishydrazone derivative 144 ) react on micropatterned catalytic sites on a surface to form building blocks of self-assembled nanofibers that act as the matrixes of the hydrogels. Unlike homogeneous catalysis, this method apparently can achieve multilevel organization among the nanofibers, which is uniquely promising for further development.…”
Section: Stimuli For Hydrogelationmentioning
confidence: 99%
“…[6] A number of strategies have emerged to shape and structure supramolecular gels, [3] including photopatterning, [7] 3D printing, [8] electrochemistry, [9] and surface-mediated processes. [10] Several reports have used controlled diffusion to achieve spatial resolution. [11] Surprisingly, however, there have been limited reports of a supramolecular gel being formulated as spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Along this route, spatial localization of (bio)catalysts has recently proven to be an effective process to direct supramolecular self-assemblies in a spatiotemporal way. [16][17][18][19][20] Localization of (bio)catalysts in space allows inducing the chemical switch from non-self-assembling entities into self-assembling ones, leading to a spontaneous self-assembly process occurring exclusively and specifically near the (bio)catalyst localization. Ulijn and co-workers have first shown that the immobilization of thermolysin on a glass substrate followed by the contact with a mixture of Fmoc-L and LL dipeptide (L=Leucine) allows the self-assembly nucleation of Fmoc-Ln spatially controlled from the enzymatically-active surface.…”
Section: Introductionmentioning
confidence: 99%